2004
DOI: 10.1016/j.clpt.2004.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isotretinoin on the pharmacokinetics and pharmacodynamics of ethinyl estradiol and norethindrone

Abstract: The small reduction in ethinyl estradiol and norethindrone levels associated with isotretinoin was not associated with any pharmacodynamic changes in our study. The combination of the teratogenic risk of isotretinoin and the large variability of and correlation between oral contraceptive levels and pharmacodynamic measures, however, strongly reinforces the necessity of additional contraceptive methods during concomitant administration of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The finding that the AUC 0–24hr and C max of EE 2 and NET were contained within the predefined comparability bounds indicates that the coadministration of sitagliptin with an oral contraceptive agent will not cause safety issues related to estrogen activity. The pharmacokinetic estimates in this study for EE 2 and NET, whether administered alone or with sitagliptin, were also similar to those reported previously for EE 2 and NET alone 13 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that the AUC 0–24hr and C max of EE 2 and NET were contained within the predefined comparability bounds indicates that the coadministration of sitagliptin with an oral contraceptive agent will not cause safety issues related to estrogen activity. The pharmacokinetic estimates in this study for EE 2 and NET, whether administered alone or with sitagliptin, were also similar to those reported previously for EE 2 and NET alone 13 …”
Section: Discussionsupporting
confidence: 89%
“…The biotransformation of NET occurs primarily by reduction followed by sulfate and glucoronide conjugations. The estimated values for t 1/2 from a previous study were 14.2 and 10.3 hours for EE 2 and NET, respectively, after 20 days of administration 13 …”
mentioning
confidence: 83%
“…There were small but statistically insignificant changes in ethinyl estradiol and norethindrone concentrations. 5 The iPLEDGE program does allow the patient and provider to agree on the use of abstinence as a primary form of contraception. Given the potential consequences of a pregnancy while on isotretinoin, it is advised that the provider feel very comfortable in the maturity of a patient that desires to use this as their form of birth control.…”
Section: Teratogenicitymentioning
confidence: 99%
“…Hendrix et al. showed that interactions occur between isotretinoin and oral contraceptive components ethinyl estradiol and norethindrone (42). Some of these interactions lower the circulating blood levels of these hormones, compromising their efficacy at pregnancy prevention.…”
Section: Acnementioning
confidence: 99%